Impact of spindle tilt and machining parameters on surface roughness in milling - Romiyadi, Romiyadi; Febrianton, Adi (Politeknik Negeri Lhokseumawe, 2025)
This study aims to analyze the influence of spindle tilt and machining parameters (feed rate, depth of cut, and spindle speed) on surface roughness in milling operations using a Knuth UFM 2 universal milling machine. A parametric experimental approach was used, where parameters were varied systematically to assess their influence on surface quality. Results show that increasing spindle tilt, feed rate, and depth of cut generally raises surface roughness, while higher spindle speeds reduce it, producing smoother surfaces. The optimal surface quality was achieved during the first up-milling test with a spindle inclination of 30°, feed rate of 108 m/min, spindle speed of 720 rpm, and depth of cut of 0.50 mm, yielding a surface roughness (Ra) of 0.258 µm. In contrast, higher tilt angles and cutting loads significantly degraded surface finish, with roughness increasing by up to 95.91% when spindle tilt was raised from 30° to 60°, by 52.86% when depth of cut increased from 0.50 mm to 1.50 mm, and by 79.25% when feed rate rose from 45 m/min to 233 m/min. Conversely, increasing spindle speed from 148 rpm to 720 rpm reduced Ra by 99.81%. These findings highlight the importance of selecting appropriate parameter combinations to achieve precision, efficiency, and sustainability in milling. The results also provide practical reference for industrial applications and vocational training in manufacturing engineering.